Row, Row, Row Your Boat - Cabrera, Jane (New York : Holiday House, 2014)
In this expansion of a familiar song, the occupants of a rowboat enjoy seeing and making the sounds of different jungle animals.
Keywords: Children's songs, English -- United States -- Texts; Animal sounds -- Songs and music; Songs; Jungle animals -- Songs and music; Boats and boating -- Songs and music